Comparative evaluation of mineral profiles in different blood specimens of dairy cows at different production phases - Hussein, Hussein Awad; Müller, Anja-Elivera; Staufenbiel, Rudolf (Frontiers in Veterinary Science, 2022)
The present research was designed to investigate the variations of mineral profiles in different blood specimens of dairy cows at different lactation stages. The concentrations of copper (Cu), zinc (Zn), selenium (Se), manganese (Mn), barium (Ba), strontium (Sr), calcium (Ca), magnesium (Mg), total phosphorous (P), sulphur (S), cobalt (Co), silicon (Si), lithium (Li), nickel (Ni), thallium (Tl), boron (B), aluminium (Al), uranium (U) and arsenic (As) were measured in serum, ethylene diamine tetraacetic acid (EDTA) plasma, heparin plasma, and EDTA whole blood samples. The concentrations of Cu, Zn, Fe, Mn, Ba and Sr showed significant variations among the dairy cows of different lactation stages (p < 0.05). Strong regressions were determined between the mineral concentrations in individual and pooled samples (R2 = 0.991, p = 0.000). In comparison with other blood sample types, the concentration of Cu, Ba and Sr was higher in EDTA plasma (p < 0.000). In addition, the values of Zn, Se, Fe and Mn were significantly increased in heparin and EDTA whole blood samples. Concentrations of Ca and Mg, and P were higher in EDTA plasma, and EDTA whole blood samples, respectively. Furthermore, the mean values of Si, Li, Ni and Tl showed significant increases in EDTA plasmas, while S values were higher in EDTA whole blood samples (p < 0.000). Concentrations of Al and U exhibited significant increases in serum samples (p < 0.000). Concentrations of Cu, Zn, Fe, Mn, Ba, and Sr undergo physiological variations among dairy cows. The concentrations of essential and toxic elements, as well as Ca, P, Mg and S varied among the different blood sample specimens, indicating their interpretations should be based on this regard. During dairy herd supervision, using of pool sample instead of individual ones for determination of mineral status may be promising to minimize the costs of individual samples’ measurements. In general, EDTA plasma may be more suitable for measurements of Ca, Mg, P, and S. It seems that EDTA plasma and heparinized plasma are suited for estimation of Se and Fe, respectively.